Mobile apps on experiential learning: a quick guide for educator / Nur Hafidah Abd Kadir ...[et al.] - Abd Kadir, Nur Hafidah; Ibrahim, Hariati; Md Naim, Irwan Affendi; Hasmin, Nor Akhmal (2018)
Educator need to explore the effective methods of teaching to create enjoyable learning environment. This research is largely based on the experience of applying experiential learning in teaching a non-law subject to law students in Centre for Foundation Studies, University Teknologi MARA. Based on the research conducted,the feedback shows that 89% respondents prefer learning environment consisting of combination of conventional method and experiential learning. Besides, research found that based on the students perception, experiential learning is an effective instrument to enhance learners’ understanding of the topics, exposing them to the real world and giving them opportunity to relate and apply the knowledge that they had gained in the classroom into a real life situation. Respondents also reported that they have acquired myriad of skills through the application of experiential learning such as teamwork, communication, technological, leadership, critical thinking and other soft skills. Thus, researchers took the initiative to design a mobile apps that serves as a quick guide for educators at all level of education to adopt experiential learning as part of their methods of teaching. The mobile apps contains explanation on experiential learning, is proven benefits to both learners and educators and examples of experiential learning activities that can assist the educators who wish to embark on this method